Сокровище антиквара: [роман] / Александр Бушков - Бушков Александр Александрович (Олма Медиа Групп, 2015)
Экземпляры: ф.17 (20160808) / Инвентарный номер: 48403 / Цена: 95.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 94 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6